2010
DOI: 10.1515/hf.2010.016
|View full text |Cite
|
Sign up to set email alerts
|

Lignin and carbohydrate variation with earlywood, latewood, and compression wood content of bent and straight ramets of a radiata pine clone

Abstract: Changes in lignin and carbohydrate content with radial direction, growth-layer number, compression wood (CW) severity, and earlywood (EW) and latewood (LW) origin are described for one near-ground position in each of a severely bent and a nominally straight ramet (tree) of a clone (genotype) of Pinus radiata. Bark-to-bark strips were taken through the pith and the longest radial dimension of the CW side of the discs. Separate EW and LW samples were obtained for most growth layers, yielding a total of 95 sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 8 publications
(14 reference statements)
2
13
0
Order By: Relevance
“…The correlations between lignin and sugar yields seen in Figure 3a and b are in good agreement with recent results for P. taeda (Chen et al 2007), except that these authors reported a linear correlation between the concentrations of lignin and galactose across both OW and CW. A trend similar to that in Figure 3a was also observed for a much larger P. radiata data set (Kibblewhite et al 2008) (Figure 3c). However, considerably more scatter is evident in this data, due both to differences in the chemical compositions of earlywood and latewood, and to the high yields of galactose in juvenile OW.…”
Section: Criteria For Cw Indicatorssupporting
confidence: 83%
“…The correlations between lignin and sugar yields seen in Figure 3a and b are in good agreement with recent results for P. taeda (Chen et al 2007), except that these authors reported a linear correlation between the concentrations of lignin and galactose across both OW and CW. A trend similar to that in Figure 3a was also observed for a much larger P. radiata data set (Kibblewhite et al 2008) (Figure 3c). However, considerably more scatter is evident in this data, due both to differences in the chemical compositions of earlywood and latewood, and to the high yields of galactose in juvenile OW.…”
Section: Criteria For Cw Indicatorssupporting
confidence: 83%
“…There was a linear relationship between galactose and Klason lignin content showing three clusters for NW, mild CW, and severe CW ( Figure 5). Changes in CW severity are associated with increased lignin and galactose contents, and decreased glucose content (Nanayakkara et al 2009;Kibblewhite et al 2010). Based on the results in the present paper it is obvious that, T control and T drought produce mild to moderate CW, while T tilting leads to severe CW (Nanayakkara et al 2009;Brennan et al 2012).…”
Section: Chemical Composition and Cw Severitysupporting
confidence: 56%
“…Drought and tilting stresses did not alter the chemical composition of NW beyond the usual between-tree variation (Kibblewhite et al 2010); however, CW chemistry was significantly affected (Table 7). CW in the T control and T drought had lignin and galactose contents of 31-33% and 5-8%, respectively, while in T tilting , lignin and galactose contents were in the range 37-40% and 9-12%, respectively ( Figure 5).…”
Section: Chemical Composition and Cw Severitymentioning
confidence: 94%
“…The neutral sugar composition of hemicelluloses are also different in TW and CW as the latter often yields a large amount of galactose, indicating that the lower cellulose content is accompanied by higher galactose and lignin contents (Timell 1969;Timell 1986;Nanayakkara et al 2009;Kibblewhite et al 2010). In TW, the lsW of a trunk will generally give rise to a relatively larger amount of xylose and thus the lower yield of glucose originating from cellulose is compensated (Timell 1969).…”
Section: Introductionmentioning
confidence: 99%